Детские годы Багрова-внука - Аксаков Сергей Тимофеевич (Золотые родники, 1977)
Экземпляры: аб. ЦБ (20220815) / Инвентарный номер: 16361 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: А 41 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1